Prevalence and factors associated with restless legs syndrome in hemodialysis patients at Muhimbili National Hospital, Tanzania - Mohamed, Shaneabbas; Msilanga, Daniel; Mngumi, Jonathan; Shoo, Jacqueline; Ruggajo, Paschal (African Journal of Nephrology, 2025)
Background: Restless legs syndrome (RLS) is a common motor-sensory disorder among chronic kidney disease patients on hemodialysis, significantly affecting quality of life. While its prevalence varies widely, there is a lack of research on RLS in African hemodialysis patients. This study aims to address this gap by assessing the prevalence, severity, and associated factors of RLS in patients undergoing HD at Muhimbili National Hospital (MNH) in Tanzania. Methods: A six-month cross-sectional study (August 2023 - January 2024) was conducted at the Muhimbili National Hospital hemodialysis unit, enrolling 348 end-stage kidney disease patients aged ≥18 years. RLS was diagnosed using the 2012 revised International Restless Legs Syndrome Study Group (IRLSSG) questionnaire, with severity assessed via the IRLSSG severity rating scale. Data were analyzed using SPSS version 23, with chi-square or Fisher's exact tests for categorical variables and binary logistic regression for associations. Statistical significance was set at p < 0.05, and ethical approval was obtained from the MUHAS ethics committee. Results: A total of 348 ESKD patients on HD at MNH were recruited, with a median age of 50 (±12) years; 244 (70.1%) were male. RLS prevalence was 10.1%, and 91% had moderate to severe RLS, with a mean score of 18 (±5). Multivariate analysis identified age ≥ 60, being underweight, HIV infection, HD inadequacy (URR <65%), and higher predialysis blood urea nitrogen (BUN) levels as independent factors associated with RLS (p < 0.05). Conclusions: Approximately 10% of ESKD patients undergoing hemodialysis at MNH experience moderate to severe RLS. Key factors include age ≥ 60, underweight status, HIV infection, HD inadequacy, and high predialysis urea levels. Regular screening for RLS and addressing these risk factors through a multidisciplinary approach involving nephrologists, nutritionists, and other healthcare professionals is recommended.